Reflecting on pronunciation instruction in the Polish English classroom: Learners’ perspective - Waniek-Klimczak, Ewa; Klimczak-Pawlak, Agata (Research in Language, 2025)
Pronunciation remains a controversial aspect of English instruction, both in theory and practice, with the dichotomy between “nativeness” and “intelligibility” (Levis, 2005) directing research into the exploration of learner and teacher views as to what they want to achieve, and, consequently, which elements of the English sound system should be included in language teaching and learning. Continuing a long tradition of questionnaire studies among Polish learners and teachers of English, this paper explores the presence of pronunciation instruction in the English classroom by inviting students who have chosen English as their BA major to reflect on their experience. The total of 70 students participated in a questionnaire study in which they were asked to reflect on whether they remembered pronunciation to have been included in their English instruction at different levels of schooling, and if it was, how it was taught and which aspects they remembered to have been practiced. They were also encouraged to provide comments and to share their views on the usefulness of instruction as well as to provide recommendations for pronunciation teaching and learning. The results show that pronunciation is only marginally present in students’ learning experience, with a slight increase corresponding to the level of schooling and a growing preference for suprasegmental phonetics. While commenting on their experience, students stress the need for pronunciation practice, correction by the teacher and self-study to be included from the beginning of EFL education.